PERAN ORANG TUA DALAM PEMBELAJARAN - sylvana Talangamin; Heldy Rogahang; Orient Christianty (Jurnal Ilmiah Wahana Pendidikan, 2021)
The Covid - 19 pandemic that has hit the world, including Indonesia, has brought changes in various spheres of life. Adapting to situations like this is the best choice. The world of education is one of the areas that has undergone significant changes. In general, the wider community thinks that school is a place to learn, in school every student is honed his cognitive abilities, even though other assessments are included such as affective and spiritual assessments. It is in school that cognitive development is experienced by a student, even teacher-student relations are important for a student's self-development towards Indonesia's goal of "educating the nation's life" but all of these things have changed due to the Covid-19 Pandemic. The teaching and learning process is no longer centered in schools but in their homes. Parents also have to adapt when their roles as teachers and parents are no longer an option but a priority. Obstacles in the learning process began to be felt starting from the difficulty of accessing the internet, quota fees that must be met and the difficulty of parents being teachers at home . This journal writing uses a descriptive qualitative method. Parents really understand their duties and responsibilities. Parents realize that children are in the digital generation. Parents understand Biblical principles regarding duties and responsibilities in accompanying children.